Saving Women, Saving Families: An Ecological Approach to Optimizing the Health of Women Refugees with S.M.A.R.T Primary Care - J. Nwando Olayiwola; Melanie Raffoul (AIMS Press, 2016)
More than 43 million people worldwide have been forcibly displaced from their homes as a result of conflict and persecution, over 50% of whom are women and 41% are children. The United Nations estimates that two-thirds of the world's refugees have been in exile for over 5 years, and more than half are in urban environments, as opposed to camps. Therefore, long-term strategies for healthcare in receiving countries are needed. The unique challenges facing refugee women as they seek safe and stable living situations are compelling. A system that optimizes the health of women refugees has significant implications for the rest of the family.